Treating Large Shell Defects and Exposed Viscera: An Excellent Prognosis for Turtles - Bogard, Chris (Wildlife Rehabilitation Bulletin, 2008)
Injured turtles typically present with moderate to severely comminuted (many pieces, crushed) shell fractures requiring management of broken pieces. Injured turtles atypically present with large shell fragments missing thereby exposing the body cavity and visceral organs. Large defects accompanied by deep soft tissue trauma can be and have been mistakenly identified as cause for euthanasia. Remarkably, the prognosis is very good for this type of trauma if treated properly.